PENGARUH PERSEPSI GURU TERHADAP TANTANGAN GREENFLATION TERHADAP SIKAP PEDULI LINGKUNGAN - Zalfa Eisna Kanaya; Wibowo, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is aims to determine the effect of teachers' perceptions of the greenflation challenge on environmental care attitudes in Elementary Schools in Group 03 Kasihan, Bantul. This research is a survey research using quantitative approach. The subjects of this research consisted of teachers and fifth grade students of elementary schools in Group 03 Kasihan, totaling 95 people. Data collection instruments through questionnaires. The results can be seen from the t test analysis data with t count (2.626) more than t table (1.661) with a significance value of 0,010. The significance value is <0,05, which means it shows the influence of teacher perceptions of greenflation challenges on environmental care attitudes and has an effect of 6.9%.